2020
DOI: 10.1002/hyp.13946
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating the longitudinal functional connectivity of a river–lake–marsh system and its application in China

Abstract: The longitudinal functional connectivity of a river-lake-marsh system (RLMS) refers to the actual water-mediated transport of material from upstream to downstream areas along a spatial gradient and is fundamental to understand hydrological and biogeochemical cycles. However, due to a lack of consensus on appropriate data and methods, the quantification of connectivity is still a challenge, especially at the catchment scale. We developed a new method to evaluate longitudinal functional connectivity based on flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In this special issue, for the research on hydrological connectivity, Liu, Cui, et al (2020) evaluated the longitudinal connectivity based on fluxes of materials (water, sediment and chemicals) in a typical river–lake‐marsh system. The results indicated that landscape patterns could significantly affect fluxes in the system and should be taken into account.…”
Section: Environmental Flow Mechanismmentioning
confidence: 99%
“…In this special issue, for the research on hydrological connectivity, Liu, Cui, et al (2020) evaluated the longitudinal connectivity based on fluxes of materials (water, sediment and chemicals) in a typical river–lake‐marsh system. The results indicated that landscape patterns could significantly affect fluxes in the system and should be taken into account.…”
Section: Environmental Flow Mechanismmentioning
confidence: 99%
“…Dong et al ( 2021 ) found that the increase in connectivity causes low spatial environmental heterogeneity and biotic homogenization of floodplain wetlands landscapes. Some studies concluded that floodplain wetlands are faced with degradation in drier seasons, causing reduction in river-floodplain connectivity (Liu et al 2020 ). In drier climate, water quality of floodplain wetlands is worse than that in flooding events (Liu et al 2020 ).…”
Section: Hydrological Connectivity At Multiscales and Its Effects On Ecohydrologymentioning
confidence: 99%
“…Some studies concluded that floodplain wetlands are faced with degradation in drier seasons, causing reduction in river-floodplain connectivity (Liu et al 2020 ). In drier climate, water quality of floodplain wetlands is worse than that in flooding events (Liu et al 2020 ). This is because surface water level in dry seasons is lower than the median main river stage, which results in the disconnectivity between the rivers and the floodplain wetlands.…”
Section: Hydrological Connectivity At Multiscales and Its Effects On Ecohydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…The landscape model is a hydrological model, which is created to measure the connectivity (Laliberté & St-Laurent 2020). The connectivity function analysis can assess the connectivity based on hydrology (Luo et al 2018a(Luo et al , 2018bWang et al 2019;Liu et al 2020), while the calculation method varies with the water source. Because of the diversification of research, graph theory is popular, which is a theoretical model that uses an abstract method to assess the relations among research objects (Ishiyama et al 2020;Feng et al 2021).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%